PARAMETERS OF ENTERPRISE INNOVATION ACTIVITY ASSESSMENTS: ECONOMIC AND LEGAL ANALYSIS - Kupriyanova, Lyudmila; Albov, Alexey; Golyshevа Ninа (Revista Inclusiones, 2020)
The paper addresses the problem of selecting the most important parameters to assess efficient enterprise development and integration; a special aspect is the comprehensive legal and economic study of enterprise development performance analysis. The findings show that social and legal effects make the forecast background of the innovation process; it is also established that the application and calculation of expert assessments should be focused, as a principal condition, on an integral assessment and establishing a correlation between different factors, namely, economic, legal, information, and resource factors. The findings may be useful for practical and research support of the economic and legal operation in advancing enterprise activity.